Analisis Problematika Pembelajaran Ilmu Nahwu dalam Pembelajaran Bahasa Arab di Kelas VIII SMP Al Anwar Panji - Sartono Hadi; Yeni Nuriah Fitri (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the problems encountered in teaching Nahwu (Arabic grammar) in Arabic language learning among eighth-grade students at SMP Al Anwar Panji and to identify the factors influencing these problems. The study employed a qualitative approach using a case study design. The participants consisted of the principal, the vice principal for curriculum, one Arabic language teacher, and four students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data credibility was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that the problems of Nahwu learning are multidimensional, resulting from the interaction of student-related, teacher-related, and learning facility factors. Students' difficulties are influenced not only by the complexity of Arabic grammatical rules but also by low learning motivation, limited independent learning habits, the dominance of lecture- and memorization-based instruction, and an unconducive learning environment. The study concludes that improving the quality of Nahwu learning requires an integrated approach through strengthening teachers' pedagogical competence, implementing active and contextual learning strategies, fostering students' independent learning habits, and providing supportive learning facilities and environments.